ANALISA IT/IS STRATEGIC PLANNING TERHADAP ADOPSI TEKNOLOGI INFORMASI DALAM KONTEKS KINERJA ORGANISASI PADA UMKM - Sani, Asrul; Pusparini, Nur Nawaningtyas; Budiyantara, Agus; Supit, Merliani Ivone; Aisyah, Siti (Infotech: Journal of Technology Information, 2023)
The research objectives to analyze the impact of Information Technology/Information Systems (IT/IS) strategic planning on the adoption of Information Technology (IT) within the context of organizational performance in Small and Medium-sized Enterprises (SMEs). In the continually evolving digital era, the ability of SMEs to integrate and effectively leverage IT is crucial for their sustainability and growth. The research methodology involves surveying and analyzing data from a range of SMEs that have implemented IT/IS strategic planning. The findings indicate a positive correlation between IT/IS strategic planning and the level of IT adoption in SMEs operations. SMEs with mature IT/IS strategic planning are more likely to efficiently implement and utilize information technology, thereby enhancing organizational performance. Factors such as budget allocation, technological literacy, and understanding the benefits of IT play a significant role in this relationship. This research contributes significantly to understanding how IT/IS strategic planning can act as a catalyst for successful IT adoption among SMEs. Practical implications of the research include recommendations for policy formulation, human resource training, and the development of technology empowerment strategies for SMEs. Thus, this research holds substantial relevance in supporting the growth and competitiveness of SMEs in the digital era.